The added diagnostic value of RT-PCR on faeces for the diagnosis of COVID-19 - Nathalie Van der Moeren; Rik van den Biggelaar; Karin B. Gast; Jaco J. Verweij; Barbara J.M. Bergmans; Joep J. J.M. Stohr; Jean-Luc Murk (PLoS ONE, 2025)
Objectives To determine whether combining a SARS-CoV-2 RT-PCR on a fecal sample [FS] with a RT-PCR on an upper respiratory tract sample [URTS] results in additional COVID-19 diagnoses. Methods We conducted a retrospective observational study at a regional hospital in The Netherlands from 27 February 2020–30 June 2020. Patients presenting with COVID-19-like symptoms for who a SARS-CoV-2 RT-PCR on both URTS and FS were obtained within 24 hours were included. We calculated the difference in positive RT-PCR when combining URTS/FS compared to URTS alone, overall and stratified by symptom duration and disease severity. Results Three hundred eighty-six patients were included of which 63 had a positive RT-PCR on URTS [n = 8], FS [n = 19] or both [n = 36], corresponding to a prevalence of 16.3%. The addition of testing FS increased the number of COVID-19 diagnoses by 31.8% [95%CI 20,3%-43,2%]. Conclusions We showed that adding SARS-CoV-2 RT-PCR on FS to URTS yields significantly more COVID-19 diagnoses. The inclusion of an FS may therefore be considered in patients with a negative URTS and high suspicion of COVID-19.